2013
DOI: 10.1063/1.4809557
|View full text |Cite
|
Sign up to set email alerts
|

Competition between uncatalyzed and catalyzed growth during the plasma synthesis of Si nanowires and its role on their optical properties

Abstract: In this paper, we study the metal-catalyzed synthesis of Si nanowires (Si-NWs) in a plasma based chemical vapor deposition system. In these deposition systems due to the high efficiency of precursor molecule dissociation, both uncatalyzed and catalyzed growth mechanisms can take place. The first one gives rise to the formation of the quasi one-dimensional (1D) Si-NWs, while the second one to a continuous two-dimensional (2D) Si layer over the substrate or on the nucleated Si-NWs. The Si-NWs formation is then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Moreover, in an inductively coupled plasma (ICP) CVD reactor, the high plasma density and the absence of acceleration of ions toward the substrate grant the absence of structural substrate damage. In reference [17], different plasma power values between 0 and 1000 W were explored to study its role on the Si NWs growth. Morphological results showed that three growth regimes can be identified: a low plasma region from 0 to 60 W, where only 1D SiNW structures were grown, an intermediate region from 60 to 100 W where both 1D and 2D films were obtained, and a third zone at high plasma power (from 100 to 1000 W) where SiNWs were absent and only continuous uncatalyzed Si layer was obtained.…”
Section: Silicon Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in an inductively coupled plasma (ICP) CVD reactor, the high plasma density and the absence of acceleration of ions toward the substrate grant the absence of structural substrate damage. In reference [17], different plasma power values between 0 and 1000 W were explored to study its role on the Si NWs growth. Morphological results showed that three growth regimes can be identified: a low plasma region from 0 to 60 W, where only 1D SiNW structures were grown, an intermediate region from 60 to 100 W where both 1D and 2D films were obtained, and a third zone at high plasma power (from 100 to 1000 W) where SiNWs were absent and only continuous uncatalyzed Si layer was obtained.…”
Section: Silicon Nanowiresmentioning
confidence: 99%
“…Many aspects dramatically controlling the NW morphology like the precursor flow gas [14], the substrate type, and crystallographic orientation [8,12,15]; the SiNWs growth direction [12] and substrate surface chemical conditions [16] will be reviewed and discussed. When SiNWs are deposited by using plasma enhanced chemical vapor deposition (CVD) systems, also the plasma power plays an important role in the formation of SiNWs [17]. The most common metal exploited as a catalyst is gold, thanks to its low eutectic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…PECVD indeed proved successful for NW growth at a relatively fast rate often below the eutectic point of the different catalysts used (e.g., Au [14][15][16]; Al [17]; Ga or In [16][17][18]). However, PECVD leads to the formation of mixed amorphous/crystalline structures, making the separation of the deposition by-products from NWs difficult [19]. A crucial point in this field is thus the ability to keep separated the nano-structure and the crystalline form of the deposited material, while working at relatively low-temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles on silicon substrates have shown quite interesting applications in the fields of Si nanowire (SiNW) catalysis [ 1 3 ], metal-assisted etching (MAE) [ 4 ] or even as electrical contacts in standard miniaturized devices [ 5 ]. Their ability to display enhanced surface plasmon resonance (SPR) at optical frequencies makes them excellent at scattering and absorbing visible light [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%